APLIKASI SISTEM MULTI AGEN PADA PENGENDALIAN TIGA KAPAL SEKALIGUS - Tjahjana, R. Heru (MATEMATIKA, 2011)
This paper presented a problem controlling the three ships as the application of multi-agent system. The multi-agent system model which used in this exposition is linear multi-agent system and the ship model which used in this paper is linear ship model from Hocking. The Control design completion for each ship used the optimal control design strategy by utilizing Pontryagin Maximum Principle. This principle leads to the classical problem of optimum control that treatment using the steepest descent method.